2021
DOI: 10.3390/su13168707
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Competence and Intrinsic Motivation in Mathematics: Exploring Latent Profiles

Abstract: This study aims to use a person-centred approach to identify possible student motivational profiles in mathematics. These profiles are made up of various combinations of two motivational variables: perceived competence and intrinsic motivation. Once the profiles are identified, we examine the differences between them in negative emotions and mathematics performance. Our sample comprised 863 students (50.2% boys, 49.8% girls) aged between 9 and 13 years old. The results indicated three motivational profiles. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
7
0
2
Order By: Relevance
“…This conclusion aligns with previous research that showed a positive and meaningful relationship between competency and motivation (Dellaportas et al, 2012;Ilomäki et al, 2016). Organizations can promote motivation among public service employees by providing opportunities for skill development, training, and recognition of their competence and creating an environment that fosters a sense of mastery, autonomy, and achievement in their roles (Rodríguez et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This conclusion aligns with previous research that showed a positive and meaningful relationship between competency and motivation (Dellaportas et al, 2012;Ilomäki et al, 2016). Organizations can promote motivation among public service employees by providing opportunities for skill development, training, and recognition of their competence and creating an environment that fosters a sense of mastery, autonomy, and achievement in their roles (Rodríguez et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Competence enhances motivation, performance feedback supports competence development, and competence and performance are linked to professional growth in public service. Public organizations must recognize and nurture the relationship between competence and performance to foster a competent and high-performing workforce (Rodríguez et al, 2021;Suriyanti, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Empirical Study of Factors Affecting Students' … International Journal of Instruction, October 2022 • Vol.15, No.4 line with the studies of Kozar and Connell (2015) and Rodríguez et al (2021). They observe that the students are eager to start the course program for expertise, read the taught material, and ask questions.…”
mentioning
confidence: 84%
“…Dandira et al (2017) also finds that the students' attention on lecturers depending on their learning interest. The effective increase in interest should focus on feelings of pleasure, student involvement, and attention (Hong, 2021;Majali, 2020;Marniati& Wibawa, 2018;Rodríguez et al, 2021). Students with learning interests can identify learning material problems and find solutions through technological sources (Cabrita et al, 2020;Shahroom&Hussin, 2018).…”
Section: The Effect Of Learning Interest On Internshipmentioning
confidence: 99%
See 1 more Smart Citation